(untitled) (Research, Society and Development, 2021)
Leisure is a non-mandatory occupation performed in free time and related to opposition to work. It may be associated with leisure, due to the cultural process, that is, the definition of this activity may vary from one social group to another. Occupation is conceived as a subjective factor for the subject, being also the central axis of Occupational Therapy. This study aimed to analyze the leisure practices and conceptions of Occupational Therapy students at a Public University in the Northeast. Exploratory and qualitative study. Composed of a semi-structured interview, with discussion axes focused on leisure activities. Data were analyzed and categorized based on Bardin’s Theory. Leisure activities were grouped and divided into two final categories - leisure activities performed within the home environment and leisure activities performed outside the home environment. The most practiced leisure activity was ’watching’ - movies, series and variety programs. The realization of them happens in a segmented way, that is, when students have free time to carry them out, not necessarily being already scheduled activities. Two obstacles that were identified as a hindering agent for the performance of leisure activities were: free time and financial issues. Leisure activities play an important role for good occupational performance and for bringing well-being and quality of life to students’ lives.